Answer:
f(3)=5
f(0)= -7
Step-by-step explanation:
replace
4(3)-7
f(3)=5
f(0)=4(0)-7
f(0)=0-7
f(0)= -7
Answer:
<h3>p = 131.25</h3>
Step-by-step explanation:
The variation p varies directly with T is written as
p = kT
where k is the constant of proportionality
To find p when T =500 we must first find the formula for the variation
That's
when p = 105 and T = 400
105 = 400k
Divide both sides by 400
<h3>
![k = \frac{21}{80}](https://tex.z-dn.net/?f=k%20%3D%20%20%5Cfrac%7B21%7D%7B80%7D%20)
</h3>
So the formula for the variation is
<h2>
![p = \frac{21}{80} T](https://tex.z-dn.net/?f=p%20%3D%20%20%5Cfrac%7B21%7D%7B80%7D%20T)
</h2>
when
T = 500
Substitute it into the above formula
That's
![p = \frac{21}{80} \times 500](https://tex.z-dn.net/?f=p%20%3D%20%20%5Cfrac%7B21%7D%7B80%7D%20%20%5Ctimes%20500)
Simplify
The final answer is
<h3>p = 131.25</h3>
Hope this helps you
Answer:
E
Step-by-step explanation:
![\bold{\text{Answer:}\quad \dfrac{-48x^4-42x^3-15x^2-5x}{(8x+7)(3x+1)}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Ctext%7BAnswer%3A%7D%5Cquad%20%5Cdfrac%7B-48x%5E4-42x%5E3-15x%5E2-5x%7D%7B%288x%2B7%29%283x%2B1%29%7D%7D)
<u>Step-by-step explanation:</u>
![.\quad \dfrac{-5x}{8x+7}-\dfrac{6x^3}{3x+1}\\\\\\=\dfrac{-5x}{8x+7}+\dfrac{-6x^3}{3x+1}\\\\\\=\dfrac{-5x}{8x+7}\bigg(\dfrac{3x+1}{3x+1}\bigg)+\dfrac{-6x^3}{3x+1}\bigg(\dfrac{8x+7}{8x+7}\bigg)\\\\\\=\dfrac{-15x^2-5x}{(8x+7)(3x+1)}+\dfrac{-48x^4-42x^3}{(8x+7)(3x+1)}\\\\\\=\large\boxed{\dfrac{-48x^4-42x^3-15x^2-5x}{(8x+7)(3x+1)}}](https://tex.z-dn.net/?f=.%5Cquad%20%5Cdfrac%7B-5x%7D%7B8x%2B7%7D-%5Cdfrac%7B6x%5E3%7D%7B3x%2B1%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B-5x%7D%7B8x%2B7%7D%2B%5Cdfrac%7B-6x%5E3%7D%7B3x%2B1%7D%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B-5x%7D%7B8x%2B7%7D%5Cbigg%28%5Cdfrac%7B3x%2B1%7D%7B3x%2B1%7D%5Cbigg%29%2B%5Cdfrac%7B-6x%5E3%7D%7B3x%2B1%7D%5Cbigg%28%5Cdfrac%7B8x%2B7%7D%7B8x%2B7%7D%5Cbigg%29%5C%5C%5C%5C%5C%5C%3D%5Cdfrac%7B-15x%5E2-5x%7D%7B%288x%2B7%29%283x%2B1%29%7D%2B%5Cdfrac%7B-48x%5E4-42x%5E3%7D%7B%288x%2B7%29%283x%2B1%29%7D%5C%5C%5C%5C%5C%5C%3D%5Clarge%5Cboxed%7B%5Cdfrac%7B-48x%5E4-42x%5E3-15x%5E2-5x%7D%7B%288x%2B7%29%283x%2B1%29%7D%7D)
1st equation—x, substitute y:
<span>3x + 2(x + 3) = 16 </span>
<span>3x + 2x + 6 = 16 </span>
<span>5x = 10 </span>
<span>x = 2 </span>
<span>y in the above equation: </span>
<span>= 2 + 3 </span>
<span>= 5 </span>
<span>Answer: x = 2, y = 5</span>